Catechol‐O‐Methyltransferase (COMT) Val158Met Polymorphism and Eating Disorders: Data From a New Biobank and Meta‐Analysis of Previously Published Studies. (22nd October 2017) - Collantoni, Enrico; Solmi, Marco; Gallicchio, Davide; Santonastaso, Paolo; Meneguzzo, Paolo; Carvalho, Andrè F.; Stubbs, Brendon; Clementi, Maurizio; Pinato, Claudia; Forzan, Monica; Cassina, Matteo; Fontana, Francesca; et al.
Abstract: Objectives: We investigated whether catechol‐ O ‐methyltransferase (COMT) Val158Met polymorphism is associated with eating disorders (EDs). Methods: We conducted a systematic literature search of studies published until 15 January 2017 and added data from the Italian ' Biobanca Veneta per i Disturbi Alimentari ' biobank, performing a meta‐analysis comparing COMT Val158Met genotype and allele frequencies in EDs and anorexia nervosa (AN) or bulimia nervosa (BN) patients versus controls. Results: Ten studies plus Biobanca Veneta per i Disturbi Alimentari (ED: n  = 920, controls: n  = 261 controls) with 3541 ED patients (AN = 2388; BN = 233) and 3684 controls were included. There were no significant group differences in COMT Val158Met alleles and genotype frequencies between patients and controls, for all EDs pooled together [range of odds ratios (ORs): 0.96–1.04, p ‐values: 0.46–0.97, I 2  = 0%] and when analysing separately patients with AN (ORs: 0.94–1.04, p ‐values: 0.31–0.61, I 2  = 0%) or BN (ORs: 0.80–1.09, p ‐values: 0.28–0.64, I 2  = 0–44%). Conclusions: Meta‐analysing data results from 11 studies and 7225 subjects show that COMT Val158Met polymorphism is not associated with EDs. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.